2016
DOI: 10.1097/iae.0000000000000805
|View full text |Cite
|
Sign up to set email alerts
|

Laser Prophylactic Treatment of the Fellow Eye in Giant Retinal Tears

Abstract: Prophylactic laser treatment of GRTs fellow eyes decreased the incidence of GRTs and limited the consequences of newly developed tears, lowering the occurrence of a macula-off retinal detachment with a consequent better final visual outcome respect to observation group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 6 publications
1
14
0
1
Order By: Relevance
“…In the observation group, 11/62 (17.8%) patients developed an RD, leading to a macula-off detachment in 9/11 patients. Similarly to our study, Ripandelli et al 6 found in the PLT group more preequatorial RDs not leading to a macula-off detachment, suggesting that the PLT prevents a localized RD to progress to a macula-off detachment. In the observation group, we found an RD in 24/51 patients (47.1%), compared with 11/62 (17.8%) patients in the study of Ripandelli et al 6 Our higher percentage of RDs might be explained by our longer follow-up, 107 months versus 40 months.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the observation group, 11/62 (17.8%) patients developed an RD, leading to a macula-off detachment in 9/11 patients. Similarly to our study, Ripandelli et al 6 found in the PLT group more preequatorial RDs not leading to a macula-off detachment, suggesting that the PLT prevents a localized RD to progress to a macula-off detachment. In the observation group, we found an RD in 24/51 patients (47.1%), compared with 11/62 (17.8%) patients in the study of Ripandelli et al 6 Our higher percentage of RDs might be explained by our longer follow-up, 107 months versus 40 months.…”
Section: Discussionsupporting
confidence: 90%
“…9 In the prophylactic 360-degree laser treatment group three patients developed an epiretinal membrane (3.8%), leading to a vitrectomy in two patients, and one patient developed a RT within 4 days. By contrast, Ripandelli et al 6 reported no epiretinal membrane formation in 98 patients. Although we do not know whether these events were related to the PLT, as they were 15 months and 31 months after PLT, we did not observe these events in the observation group.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Dodatkowo przed planowaną operacją zaćmy i porodem oraz w przypadku, kiedy odwarstwienie wystąpiło w drugim oku można wykonać fotokoagulację z powodu zwyrodnień kraciastych [19]. Profilaktyczne leczenie fotokoagulacją siatkówki w oku bez jakichkolwiek zmian zwyrodnieniowych zaleca się u pacjentów, u których wystąpiło przedarcie olbrzymie w drugim oku [19,22]. W takich przypadkach ryzyko odwarstwienia w oku towarzyszącym jest bardzo wysokie, sięga 65% [19,23].…”
Section: Laser W Przedarciach I Zwyrodnieniach Siatkówkiunclassified